The effect of using the educational game Quizizz on student motivation and math learning in grade 8 - Nikola, Dimas Ananda; Harini, Esti; Taufiq, Irham (Universitas Sarjanawiyata Tamansiswa, 2024)
The integration of technology in education has introduced innovative tools to enhance learning experiences, including the use of educational games. This study examines the impact of the educational game Quizizz on the motivation and mathematics performance of eighth-grade students. The research utilized a quasi-experimental design with a Non-Equivalent Control Group Design. The sample was selected using cluster random sampling, consisting of 25 students from class VIII B as the control group and 25 students from class VIII C as the experimental group. Data were collected through questionnaires and mathematics tests. The analysis employed an Independent Sample t-Test to evaluate the effect of Quizizz on student motivation and a Mann-Whitney test to assess its impact on mathematics learning outcomes. The results revealed a significant positive effect of Quizizz on motivation, with a p-value of 0.042 (p < 0.05). Similarly, Quizizz significantly improved mathematics learning outcomes, as indicated by the Mann-Whitney test (p = 0.047). These findings suggest that Quizizz is an effective interactive learning tool that enhances both student motivation and academic achievement in mathematics. Thus, incorporating Quizizz into classroom activities can be a strategic approach to fostering student engagement and improving learning outcomes in mathematics.